Influence of Students’ Mental and Physical Performance on Development of Technical and Tactical Skills in Fencing - Кривенцова, І. В.; Пашкевич, C. А.; Чистяков, С. А. (Physical Education Theory and Methodology, 2016)
Study objective: to reveal the relations between the indicators of physical and mental performance and the development of technical and tactical skills in fencers, to determine the significant criteria and tests for selecting students for health-improving and sports fencing groups. Methods: study and analysis of literature; pedagogical observations; physiological methods (physical performance by the Harvard step test with HSTI (Harvard step test Index) calculation, mental performance by the correction tables, special exercises to assess fencers’ technical and tactical skills); statistical methods. The reference group students (9 female fencers) had five workouts a week, the students (13 female students) of test group 1 (TG1) had 2 hours of physical training per week, the TG2 and TG3 (8 and 10 female students respectively) had 4 hours of fencing workouts per week. The TG2 had 4 months of fencing experience, and TG3 had one year and 4 months thereof. Results. The reciprocal effects of the performance indicators and the correlation between the indicators of technical and tactical skills of the student fencers allowed to establish the informative value of individual indicators for quality selection of students for the fencing group. The Harvard step test index and the standardized number of errors of the correction test can serve as the prognostic criteria for developing technical and tactical skills in student fencing.